2020
DOI: 10.1016/j.carbpol.2020.116305
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose nanofibrils and silver nanowires active coatings for the development of antibacterial packaging surfaces

Abstract: Cellulose nanofibrils and silver nanowires active coatings for the development of antibacterial packaging surfaces Hugo Spieser (Validation) (Investigation) (Writing -original draft) (Writing -review and editing) (Visualization), Aurore Denneulin (Conceptualization) (Writing -review and editing) (Supervision) (Funding acquisition), Davide Deganello (Writing -review and editing) (Supervision), David Gethin (Writing -review and editing) (Supervision), Rajesh Koppolu (Investigation) (Writing -review and editing),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…It was proved that AgNPs and AgNWs showed effective antibacterial activity on both Gram negative and Gram positive bacteria. 14,38,[50][51][52][53][54] Moreover, in the presence of AgNPs, the bacterial activity of E. coli is usually higher than that of Staphylococcus aureus. 52 Therefore, E. coli was selected to determine the antibacterial activity based on the diameter of the growth inhibition zone in this wok.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…It was proved that AgNPs and AgNWs showed effective antibacterial activity on both Gram negative and Gram positive bacteria. 14,38,[50][51][52][53][54] Moreover, in the presence of AgNPs, the bacterial activity of E. coli is usually higher than that of Staphylococcus aureus. 52 Therefore, E. coli was selected to determine the antibacterial activity based on the diameter of the growth inhibition zone in this wok.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…Coating is introduced onto the surface of an engraved roll, then it is partially submersed in or by an enclosed applicator head that holds the coating against the roll [131]. [132][133][134] Each method can be considered a valid technique for wet coating application and the specific choice depends on the physico-chemical features of the coating and the surface properties of the chosen substrate. For instance, coatings based on polysaccharides or proteins exhibit a considerably polar component in terms of surface energy, while the cutin, composed of ω-hydroxy acids, forms hydrophobic films [135].…”
Section: Liquid Bio-based Coatingsmentioning
confidence: 99%
“…The lactic acid-coated film has been reported to reduce the 49% oxygen transmission rate and 47% water transmission rate. 24 Silver nanoparticles polyvinylpyrrolidone (PVP)-based glycerosomes has been used as a coating, and it was reported to increase the shelf life of fresh-cut bell pepper for 12 days at 4 C. 25 In a study, the incorporation of Accasellowiana extract and silver nanoparticles in polyethylene oxide films has been reported to show the antimicrobial and antioxidant properties other than the preferred mechanical properties. Also, the film is biodegradable, which can be used as an innovative food packaging material.…”
Section: Applications Of Silver Nanoparticle In Food Packagingmentioning
confidence: 99%
“…It has been reported that the former showed high transparency and antimicrobial properties opposing gram‐negative E. coli and gram‐positive Staphylococcus aureus bacteria. The lactic acid‐coated film has been reported to reduce the 49% oxygen transmission rate and 47% water transmission rate 24 . Silver nanoparticles polyvinylpyrrolidone (PVP)‐based glycerosomes has been used as a coating, and it was reported to increase the shelf life of fresh‐cut bell pepper for 12 days at 4°C 25 .…”
Section: Applications Of Silver Nanoparticle In Food Packagingmentioning
confidence: 99%